Spermatogonial stem cell sensitivity to capsaicin: An in vitro study - Ozer Aytekin; Erdost Hatice; Gadella Bart M; Mizrak Sefika C; van Pelt Ana MM; van Dissel-Emiliani Federica MF (BMC, 2008)
Abstract Background Conflicting reports have been published on the sensitivity of spermatogenesis to capsaicin (CAP), the pungent ingredient of hot chili peppers. Here, the effect of CAP on germ cell survival was investigated by using two testis germ cell lines as a model. As CAP is a potent agonist of the transient receptor potential vanilloid receptor 1 (TRPV1) and no information was available of its expression in germ cells, we also studied the presence of TRPV1 in the cultured cells and in germ cells in situ. Methods The rat spermatogonial stem cell lines Gc-5spg and Gc-6spg were used to study the effects of different concentrations of CAP during 24 and 48 h. The response to CAP was first monitored by phase-contrast microscopy. As germ cells appear to undergo apoptosis in the presence of CAP, the activation of caspase 3 was studied using an anti activated caspase 3 antibody or by quantifying the amount of cells with DNA fragmentation using flow cytometry. Immunolocalization was done with an anti-TRPV1 antibody either with the use of confocal microscopy to follow live cell labeling (germ cells) or on Bouin fixed paraffin embedded testicular tissues. The expression of TRPV1 by the cell lines and germ cells was confirmed by Western blots. Results Initial morphological observations indicated that CAP at concentrations ranging from 150 uM to 250 uM and after 24 and 48 h of exposure, had deleterious apoptotic-like effects on both cell lines: A large population of the CAP treated cell cultures showed signs of DNA fragmentation and caspase 3 activation. Quantification of the effect demonstrated a significant effect of CAP with doses of 150 uM in the Gc-5spg cell line and 200 uM in the Gc-6spg cell line, after 24 h of exposure. The effect was dose and time dependent in both cell lines. TRPV1, the receptor for CAP, was found to be expressed by the spermatogonial stem cells in vitro and also by premeiotic germ cells in situ. Conclusion CAP adversely affects spermatogonial survival in vitro by inducing apoptosis to those cells and TRPV-1, a CAP receptor, may be involved in this effect as this receptor is expressed by mitotic germ cells.